The Effect of Sales Growth, Profitability, Leverage and Liquidity on Financial Distress Conditions at Transportation Sub-Sector Companies Listed in Indonesia Stock Exchange (IDX) - Yusril Yusril; Candra Dwi Hardiana; Suparyati Suparyati (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
Financial distress is a condition that shows the stages of decline in the company's financial condition that occurred prior to the bankruptcy or liquidation. The purpose of this research is conducted to examine: (1) The effect of sales growth on financial distress conditions in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX). (2) The effect of profitability on financial distress conditions in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX). (3) The effect of leverage on financial distress conditions in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX). (4) The effect of liquidity on financial distress conditions in transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX). The populations in this research are 45 transportation companies listed on the IDX for the 2013-2017 period. Sampling using purposive sampling method (based on criteria). Companies that meet the criteria to be sampled in this study amounted to 12 companies. The type of data used is secondary data obtained from the Indonesian Stock Exchange (IDX). The data analysis technique used is panel data regression with a common effect model. The results of the analysis of this study state that sales growth and profitability do not have a significant effect on financial distress conditions. While the results of leverage and liquidity show a significant influence on financial distress conditions. The type of data used is secondary data obtained from the Indonesian Stock Exchange (IDX). The data analysis technique used is panel data regression with a common effect model. The results of the analysis of this study state that sales growth and profitability do not have a significant effect on financial distress conditions. While the results of leverage and liquidity show a significant influence on financial distress conditions. The type of data used is secondary data obtained from the Indonesian Stock Exchange (IDX). The data analysis technique used is panel data regression with a common effect model. The results of the analysis of this study state that sales growth and profitability do not have a significant effect on financial distress conditions. While the results of leverage and liquidity show a significant influence on financial distress conditions.